Consumer behavior on social networks during the pandemic. Manabí, Ecuador 2021 - Carbache Mora, César; Lemoine Quitero, Frank; Chukwugozie Okafor, Christopher (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
This study aims to analyze consumer behavior in the use of social networks during the pandemic in Manabí, Ecuador. The methodology applied was qualitative - descriptive based on an online survey with 19 items applied to a population sample of 238 people from all over the province where social and cultural aspects, purchasing behavior, eating habits and consumption, relationships were consulted. with the family and the mitigation of stress produced by confinement. The main results were that the connectivity time was 80,7 % daily; the most used networks WhatsApp by 41,1 % and Facebook by 35,2 %; The content that attracted the most attention was the audiovisual content in 41,2 % in the format of stories with 43,7 %. That 39,1 % bet on a preference for local consumption, since security is in the first order with 69,3 %. Data that allow foreseeing that buyers should be approached by brands with more human content with a high dose of emotion.